Poland in a stage of system transformation and integration with the European Union - Tomaszyk, Mikołaj (My University, 2013)
Eight years of Polish membership in European Union can be present from several or even a dozen of research perspectives. Interesting studies are these related to absorption of assets from European Structural Funds. Especially these concerning methods of availing them and a legal state of territories strengthened according to additional financial sources. Furthermore analysis concerning activity of Polish Members of European Parliament and also these describing status of Poland in the European Community. The status as a consequence of valid treaties or even the Lisbon Treaty which is intended to replace the earlier one.
Present article is an attempt to present Polish history from two perspectives. Both system transformation and integration with the European Union are in mutual dependence. Moreover the process of integration would not be possible without an attainment of system transformation. The transformation can be measured by comprehension with Copenhagen Criteria which were drown up in 1993. The Criteria have to be fulfilled before the accession to the European Union.
Keywords: system transformation; integration with the European Union; Poland access in to the EU; Polish European policy; Lisbon Treaty; Transformation of Polish policy system